Plasma levels of carboxypeptidase U (CPU, CPB2 or TAFIa) are elevated in patients with acute myocardial infarction. (12th November 2015) - Leenaerts, D.; Bosmans, J. M.; van der Veken, P.; Sim, Y.; Lambeir, A. M.; Hendriks, D.
Summary: Background: Two decades after its discovery, carboxypeptidase U (CPU, CPB2 or TAFIa) has become a compelling drug target in thrombosis research. However, given the difficulty of measuring CPU in the blood circulation and the demanding sample collecton requirements, previous clinical studies focused mainly on measuring its inactive precursor, proCPU (proCPB2 or TAFI). Objectives: Using a sensitive and specific enzymatic assay, we investigated plasma CPU levels in patients presenting with acute myocardial infarction (AMI) and in controls. Methods: In this case–control study, peripheral arterial blood samples were collected from 45 patients with AMI (25 with ST segment elevation myocardial infarction [STEMI], 20 with non‐ST segment elevation myocardial infarction [NSTEMI]) and 42 controls. Additionally, intracoronary blood samples were collected from 11 STEMI patients during thrombus aspiration. Subsequently, proCPU and CPU plasma concentrations in all samples were measured by means of an activity‐based assay, using Bz‐ o ‐cyano‐Phe‐Arg as a selective substrate. Results: CPU activity levels were higher in patients with AMI (median LOD‐LOQ, range 0–1277 mU L −1 ) than in controls (median < LOD, range 0–128 mU L −1 ). No correlation was found between CPU levels and AMI type (NSTEMI [median between LOD‐LOQ, range 0–465 mU L −1 ] vs. STEMI [median between LOD‐LOQ, range 0–1277 mU L −1 ]). Intracoronary samples (median 109 mU L −1, range 0–759 mU L −1 ) contained higher CPU levels than did peripheral samples (median between LOD‐LOQ, range 0–107 mU L −1 ), indicating increased local CPU generation. With regard to proCPU, we found lower levels in AMI patients (median 910 U L −1, range 706–1224 U L −1 ) than in controls (median 1010 U L −1, range 753–1396 U L −1 ). Conclusions: AMI patients have higher plasma CPU levels and lower proCPU levels than controls. This finding indicates in vivo generation of functional active CPU in patients with AMI.